SOCIALIZATION STRATEGY TO INSTILL NATIONALISM IN 3T (FRONTIER, LEAST DEVELOPED, OUTERMOST) REGIONS TO COUNTER THE NATIONAL DEFENSE THREATS - Putri, Hariswati Rachmadani; Lathifatuddini, Lathifatuddini (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
The 3T region (terdepan, tertinggal, terluar or frontier, least developed, outermost) in Indonesia is an area that is prone to non-military threats, especially ideological threats that can affect national defense. Various efforts have been made by the government but the level of success achieved is still minimal. In this case, the state needs to seriously develop steps to socialize the attitude of nationalism, especially to people in the 3T region. The purpose of this study was to explore the appropriate socialization strategy used in inculcating the attitude of nationalism in the 3T society regions. This study used qualitative methods with data collection through library research and analytical methods using descriptive analysis. The results of this study are expected to find the right socialization strategy that should be applied in the 3T region in the future. The success in efforts to socialize the planting of nationalism in the 3T region by the government depends on many factors, and the involvement of the central government and regional parties, as well as all levels of society, is an important aspect in determining the success of these efforts.